Medical students’ perspectives on the anatomy course at the University of Zimbabwe - R Siwela; G Mawera (South African Medical Association, 2017)
Background. Traditional academic-led anatomy teaching methods, such as didactic lectures and cadaver dissections, are on the decline, as more student-led teaching methods are being adopted.Objectives. To assess medical students’ perspectives on the teaching objectives achieved by traditional teaching methods (lectures, cadaver dissections and tutorials) used in the anatomy course.Methods. A cross-sectional survey comprising a matrix questionnaire was performed among selected 1st-year - 5th-year medical students, using stratified random sampling. The students were requested to select a score between 0 and 5 to represent the fit between the learning outcome and the teaching method, with 0 being no fit and 5 representing a perfect fit.Results. Lectures had the highest mean score of 3.871 for the ability to provide medical vocabulary. Cadaver dissection had the highest mean score of 3.488 for its ability to develop team skills. The highest mean score of 3.415 for all three teaching methods combined was recorded for the learning outcome relating to imparting an anatomical foundation, while the lowest mean score of 2.731 was recorded for the development of skills in order to follow complicated instructions. However, no teaching method had an excellent fit (mean ≥4.5) with any of the teaching objectives.Conclusion. The study showed that the three teaching methods being used in the anatomy course were, to a great extent, useful to impart the skills and content base. However, other teaching methods, such as problem-based and team-based learning, have to be considered to achieve the other important learning outcomes.